Developing effective L2 communication strategies abroad and at home. Issue 5 (20th October 2019) - Montero, Lidia
ABSTRACT: This study looks into the effect of L2 learning context and different types of L2 exposure on changes in the use of communication strategies (CS). Previous findings on the possible effects of study abroad (SA) experiences on the development of CS do not allow for a clear conclusion on the issue. The present study specifically compares the effects on 65 Spanish undergraduate students with English as an L2 of either four months of SA experience or of AH courses, incorporating an analysis of the type of L2 contact participants engaged in, such as their relationships and leisure activities. This possible effect is measured in terms of development of CS effectiveness over a four-month period. The results suggest that engaging in non-language-oriented organised leisure activities may benefit L2 learners in developing effective CS use, with implications for language teaching and learning in both contexts.